kamaugawar and the creation of a dystopian reality: A study in hassan Blasim’s "Crossword" and Ambrose Bierce’s "Chi - Siham Hattab Hamdan, Dr. (lark, 2021)
The study shows how war can create a dystopian reality worse than the reality depicted in the dystopian stories. War creates a circular or enclosed world that has no exit where people cannot see the end of the tunnel. The study discusses two short stories, one is for the Iraqi writer Hassan Blasim entitled "Crosswords" and the other for the American writer Ambrose Bierce entitled "Chickamauga". These two short stories fit one of the categories of dystopian fiction where the society witnesses the effects of war and civilians and soldiers become the victims. Though the two stories do not adhere to the futuristic perspective of dystopian fiction, they could express the thought of their writers’ that what is going on in the society though it is real but it is at the same time, dystopian. Key Words: Dystopia, War, Defamiliarization, Hassan Blasim, Ambrose Bierce.